Prevalence of overweight and obesity among medical college students, Bengaluru - Gudegowda, Kishore S.; Vengatesan, Subathra; Sobagiah, Ranganath T. (International Journal Of Community Medicine And Public Health, 2018)
Background: Worldwide obesity has more than doubled since 1980. Stress is the major factor which contributes to obesity. Medical education is highly stressful. Even though medical students should be extra conscious about overweight and obesity, its prevalence was found out to be high among them. So this study was done with the aim to estimate the prevalence of overweight and obesity among the Medical College students and also to assess the factors influencing it. Methods: A cross-sectional study was conducted among second and third year medical students of Bangalore Medical College and Research Institute, Bengaluru, from July- September 2014. Informed written consent was obtained from the study participants after explaining the purpose of study. Out of 494 students, 424 had willingly participated in the study. Data was collected using a pre-tested, semi-structured, self administered questionnaire. Anthropometric measurements were taken. Descriptive statistics was used to analyze the data. Results: The prevalence of overweight and obesity were 14.6% and 11.3%. Overweight and obesity were more observed in boys (9.7%, 6.8%) than girls (5%, 4.5%). 25.9% girls & 11.1% boys were considered to have central obesity. 74.5% overweight/obese often feel stress at time of exams and 56.0% among them eat more during exams. Conclusions: The prevalence was found to be high among medical college students which were contributed by various factors. This can be reduced by modifying their diet, engaging in regular physical activity.